Impact of goodwill on capital structure and the moderating role of investors' education. (25th January 2022) - Thakur, Oli Ahad; Noordin, Bany‐Ariffin Amin; Matemilola, Bolaji Tunde; Alam, Md. Kausar; Setiawan, Doddy
Abstract : This paper investigates the impact of goodwill on capital structure and how investors' education affects the relationship between goodwill and capital structure in developing and developed countries. This study covers both developing and developed countries using a sample of 4912 and 4303 non‐financial companies from 23 developing and 9 developed countries, respectively, over 9 years (2010–2018). By applying panel data techniques, study shows that goodwill has a significant positive impact on the capital structure of developing and developed countries. Besides, investors' education moderates the relationship between goodwill and capital structure, especially in developed countries. Managers of the goodwill assets‐based companies in developing and developed countries can formulate their borrowing policy in the same fashion as the managers of a tangible asset‐based company do. Outcomes of this study will help investors/creditors in those countries to develop a clear view of the collateralization of goodwill. Policymakers in the developed countries will have a better idea about the role of investors' education in the financing of the companies.